P Pelatihan Penulisan Karya Ilmiah bagi Guru Geografi di Kabupaten Tasikmalaya - Satiyasih Rosali, Ely; Fadjarajani, Siti; As'ari, Ruli; Hakim, Erwin Hilman; Mulyanie, Erni; RS, Esta Rendra; Indrianeu, Tineu (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2024)
Professional competence is one of the four core competencies that teachers must possess. The ability to write and publish scientific papers is a crucial aspect of sustainable professional development. Based on observations, many geography teachers have yet to understand the structure and process of scientific writing effectively. A community service program conducted by the team from the Geography Education Study Program at Universitas Siliwangi, in collaboration with the Geography Subject Teachers' Forum (MGMP) of Tasikmalaya Regency, is a strategic step to enhance the professional competence of teachers, particularly in terms of scientific publication. This community service program focuses on scientific writing techniques, from concept dissemination to hands-on practice in writing, centered on themes of interest to the teachers. This method involves the development of technical skills, such as constructing research instruments, and builds teachers' confidence in publishing their work in scientific journals. With ongoing workshops and mentoring, the outcome is teachers' ability to write and publish scientific papers. This effort not only strengthens professionalism but also enriches knowledge in geography education. Keywords: Training; Scientific Writing; Geography Teacher